1973
DOI: 10.1159/000122185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Administration of L-Dopa on Serum Concentrations of Follicle-Stimulating Hormone (FSH) and Luteinizing Hormone (LH) in Patients with the Amenorrhea-Galactorrhea Syndrome

Abstract: The effect of acute L-dopa therapy on serum FSH and LH concentrations was studied in 10 patients with the amenorrhea-galactorrhea syndrome. L-dopa ingestion was not followed by a significant alteration in serum FSH and LH levels during a 360 min observation period. Our data indicate that L-dopa given in a single dose causes no changes in serum FSH and LH concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…Nonetheless, our findings lend further support to the idea that dopaminergic neuronal activity may play an important role in the regulation of LH secretion in humans (19). The effect of L-dopa on gonadotropin release has been examined by several investigators in the past (9)(10)(11)(12)(13). The failure to disclose a clear effect is due to the fact that most of these earlier investigators were looking for a rise rather than for a fall in LH levels (9)(10)(11).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Nonetheless, our findings lend further support to the idea that dopaminergic neuronal activity may play an important role in the regulation of LH secretion in humans (19). The effect of L-dopa on gonadotropin release has been examined by several investigators in the past (9)(10)(11)(12)(13). The failure to disclose a clear effect is due to the fact that most of these earlier investigators were looking for a rise rather than for a fall in LH levels (9)(10)(11).…”
Section: Discussionsupporting
confidence: 82%
“…The effect of L-dopa on gonadotropin release has been examined by several investigators in the past (9)(10)(11)(12)(13). The failure to disclose a clear effect is due to the fact that most of these earlier investigators were looking for a rise rather than for a fall in LH levels (9)(10)(11). Their reasoning stemmed from the experimental data in rats which indicated that dopamine enhances the release of hypothalamic LRF (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation